The Educational Philosophies of Pre-service English Teachers in Indonesia - Nurhayati, Titin; Ena, Ouda Teda (Makassar State University, 2025)
Abstract. Understanding educational philosophy is very important because it will influence the quality of education. Educational philosophy affects the teacher's decision to determine the educational purpose embedded in the curriculum and instruction. Hence, investigating the educational philosophy of the pre-service English teacher is essential because this is when the journey begins to become an English teacher. This research aimed to explore pre-service English teachers' educational philosophies and predict the consequences of their dominant educational philosophies. The data were collected from 78 pre-service teachers in the English education department at one of the state universities in Central Java. The finding showed that pre-service English teachers have a mixture of several educational philosophies, of which humanism was the dominant educational philosophy. Institution, culture, and policy influence pre-service English teachers' educational philosophy. In humanism, the teacher believes that teaching and learning processes have to give freedom to the students to develop their values. These findings provide valuable insight for education policymakers to support the development of suitable education. Keywords: curriculum, educational philosophy, pre-service English teacher, humanism